2019
DOI: 10.3390/ijerph16214258
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Teen-Informed Coding Tool to Measure the Power of Food Advertisements

Abstract: The food-related information environment, comprised of food and beverage advertising within one’s surroundings, is a growing concern for adolescent health given that food marketing disproportionately targets adolescents. Despite strong public interest concerning the effects of food marketing on child health, there is limited evidence focused on outdoor food advertising in relation to teenage diets, food purchasing, and perceptions. Further, limited research has considered both the exposure to and influence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 66 publications
0
21
0
Order By: Relevance
“…The techniques in the CAP tool also appear to mirror those covered in existing or emerging children’s marketing regulations, with the addition of broad techniques that are important to monitor due to their contribution to marketing power. It is important to note, however, that that the CAP tool’s marketing power score weighs the presence of each technique equally (i.e., one point each), but it is possible that certain marketing techniques are more persuasive to children than others [ 17 , 21 ], and therefore contribute disproportionately to the power and influence of the marketing message. The power of specific marketing techniques in relation to—or in combination with—other techniques was not tested here and should be the aim of future research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The techniques in the CAP tool also appear to mirror those covered in existing or emerging children’s marketing regulations, with the addition of broad techniques that are important to monitor due to their contribution to marketing power. It is important to note, however, that that the CAP tool’s marketing power score weighs the presence of each technique equally (i.e., one point each), but it is possible that certain marketing techniques are more persuasive to children than others [ 17 , 21 ], and therefore contribute disproportionately to the power and influence of the marketing message. The power of specific marketing techniques in relation to—or in combination with—other techniques was not tested here and should be the aim of future research.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that the frequency of marketing exposure and the number of marketing instances displayed on a food package increases the power of the marketing message [ 19 , 20 ], and could therefore influence the children’s attraction to these foods. The type of marketing techniques employed by manufacturers can also alter persuasiveness [ 17 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One challenge with the existing literature on teenagers and food marketing is that very little of it engages with the actual content of the marketing message. With the exception of a few studies [9,20], the specific persuasive techniques used within the advertisements are glossed over. To date, only one study [9] engages with the persuasive techniques found within marketing found across a spectrum of platforms.…”
Section: Introductionmentioning
confidence: 99%
“…This is concerning, as youth are highly susceptible to advertisements for potentially harmful products, including vapes (Krugman 2016 ). An increasing body of literature recognizes the influence of advertising in the retail environment on health-related behaviours (Bowman et al 2019 ; Mantey et al 2016 ). For example, a study of students in New Jersey found that individuals attending schools with greater retailer-based vaping advertisements within a half-mile were significantly more likely to have vaped in the past month (Giovenco et al 2016a ).…”
Section: Introductionmentioning
confidence: 99%